Best Answer

Assume the expression is:

4/(x + 2) + 6/(x + 5)

Simplify this expression by combining the expressions altogether. Let's go step by step.

Step 1: Determine the LCD of the expression.

The LCD of the expression is (x + 2)(x + 5). Multiply the top and bottom of each fractional expression by whatever factor the denominator is missing!

4/(x + 2) * (x + 5)/(x + 5) + 6/(x + 5) * (x + 2)/(x + 2)

Step 2: Combine the expression and simplify.

(4(x + 5) + 6(x + 2))/((x + 2)(x + 5))

= (4x + 20 + 6x + 12)/((x + 2)(x + 5))

= (10x + 32)/((x + 2)(x + 5))

🙏

🤨

😮

Study guides

Q: How do you simplify this 4 over x plus 2 plus 6 over x plus 5?

Write your answer...

Submit

Related questions

-2

f+4(f-2)

Factor it out: (x+2) squared

It is: b+4 when simplified

2

You can divide the integers in this case - 4 divided by 2 and 9 divided by 3. You would get 2 over x plus 3 over x. 4/2x + 9/3x = 2/x + 3/x = 5/x

2

i don't know does any body else know?

It is: 2c+8

To 1/2

A half = 1 over two = 1/2

No, it cannot be simplified.

is eassy

2

Yes. There highest common factor is 2, so if you divide both parts by 2, you will simplify it. That gives 1 over 4.

1over 2 is equivalent to 2 over 4 so the answer is 1 and 1 over 41 and 1 over 4 multiply the first fraction's top and bottom number by 2 to get 2 over 4 plus 3 over 4 then add across 2 plus 3 is 5 and keep the bottom number the same. Then simplify to 1 and 1 over 41/2 + 3/42/4 + 3/4 = 5/41 1/41/2 + 3/4 =2/4 + 3/4 =5/4 or 1 & 1/4

4 over fifty or 2 over 25

Yes, if you simplify it, you get 1/2

22/4 = 11/2

6/4 simplified = 3/2

it simplifies to 1/2

8/4 =2

It is: 2/8 = 1/4 simplified

5/ 2 -4/ 5 plus 2 expression can be written in simple form as 37/10.

2/5(9-7)/(1+4)Simplify 9-7 to 2.2/(1+4)Simplify 1+4 to 5.2/5